2012
DOI: 10.1016/j.dental.2011.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Standardizing failure, success, and survival decisions in clinical studies of ceramic and metal–ceramic fixed dental prostheses

Abstract: “Nothing worthwhile is ever without complications.”– Nora Roberts The recent increase in reports from clinical studies of ceramic chipping has raised the question of which criteria should constitute success or failure of total-ceramic prostheses. Terminology such as minor chipping[1], partial chipping, technical complications[2, 3], and biological complications have crept into the dental terminology and they have complicated our classification of success and failure of these crown and bridge restorations. Some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
163
0
12

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(191 citation statements)
references
References 18 publications
(17 reference statements)
2
163
0
12
Order By: Relevance
“…Another limitation has to do with the reliability of our laboratory measurements. In this study, we have chosen fracture toughness, flexural strength, and elastic modulus as reliable parameters because they have been commonly known as good clinical predictors from past literature even though there was no proven association, at least in clinical dentistry, between these parameters and their clinical outcomes [62,63].…”
Section: Future Researchmentioning
confidence: 99%
“…Another limitation has to do with the reliability of our laboratory measurements. In this study, we have chosen fracture toughness, flexural strength, and elastic modulus as reliable parameters because they have been commonly known as good clinical predictors from past literature even though there was no proven association, at least in clinical dentistry, between these parameters and their clinical outcomes [62,63].…”
Section: Future Researchmentioning
confidence: 99%
“…There is growing evidence that the incidence of chipping increases on full-ceramic restorations, which in turn has raised the question as to which criteria should determine the "success" or the "failure" of an all-ceramic restoration [25]. Terminologies such as "minor-major" chipping [46][47][48] and "technical complications" [3,49] have blurred the issue as to how the severity of a fracture should be quantified.…”
Section: Assessing the Severity Of Fracturesmentioning
confidence: 99%
“…Noteworthy, in their systematic review, Heintze et al [4] attempted to solve the problem by grading veneer chippings from 1 to 3 according to their severity and treatment options. Problematically, the authors did not list the clinical criteria that corresponded to each degree of severity [25]. Moreover, the authors concluded that a better description of the type of veneer fractures or material failures was needed based on the size and location of the breakage.…”
Section: Assessing the Severity Of Fracturesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, clinical failures of these kinds of restorations range between 13.0% at 3 years and 15.2% at 5 years (1)(2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%